A Multiplayer Case Based Story Engine - Fairclough, Chris; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 2003)
This paper describes the development of an expert casebased character director system which dynamically generates and controls a story, which is played out in a multiplayer networked game world. The system handles multiple users in a game world and directs the non player characters therein to perform for the users parallel storylines, interweaving character roles in each story. The story is told through a `narrative of actions? and automatically generated dialogue. Much of the storytelling approach is based on the seminal work of Vladimir Propp, to which is applied the AI case based planning paradigm. Initial analysis of the system is based on a review of the system and its output, but future work will involve developing a more objective format for analysis.
Keywords: Interactive story; multiplayer; case based planning; believable agents